Changes to the ACGME Common Program Requirements and Their Potential Impact on Emergency Medicine Core Faculty Protected Time. Issue 3 (19th January 2020) - Greenberger, Sarah M.; Finnell, John T.; Chang, Bernard P.; Garg, Nidhi; Quinn, Shawn M.; Bird, Steven; Diercks, Deborah B.; Doty, Christopher I.; Gallahue, Fiona E.; Moreira, Maria E.; Ranney, Megan L.; Rives, Loren; et al.
Abstract: The Accreditation Council for Graduate Medical Education (ACGME), which regulates residency and fellowship training in the United States, recently revised the minimum standards for all training programs. These standards are codified and published as the Common Program Requirements. Recent specific revisions, particularly removing the requirement ensuring protected time for core faculty, are poised to have a substantial impact on emergency medicine training programs. A group of representatives and relevant stakeholders from national emergency medicine (EM) organizations was convened to assess the potential effects of these changes on core faculty and the training of emergency physicians. We reviewed the literature and results of surveys conducted by EM organizations to examine the role of core faculty protected time. Faculty nonclinical activities contribute greatly to the academic missions of EM training programs. Protected time and reduced clinical hours allow core faculty to engage in education and research, which are two of the three core pillars of academic EM. Loss of core faculty protected time is expected to have detrimental impacts on training programs and on EM generally. We provide consensus recommendations regarding EM core faculty clinical work hour limitations to maintain protected time for educational activities and scholarship and preserve the quality of academic EM.